MODERN HEALTH TECHNOLOGIES OF RECOVERY HEALTH OF ATHLETES (Physical Culture and Sport: Scientific Perspective, 2022)
In Ukraine, as in the whole world, the use of SPA technologies is growing in popularity. SPA services, SPA procedures, SPA massage, SPA technologies, SPA resort, SPA area, etc. – these concepts are today associated with disease prevention, recovery, treatment and recovery. SPA is a term widely used in the West, which is defined in academic dictionaries as "a spa or natural spring of thermal or mineral water used for drinking and bathing for the purpose of health and treatment of various diseases." This popular word in our country is probably derived from the name of the town of Spa (Spa) in the province of Liège (Eastern Belgium). The city of Spa (Spa) has been known since ancient Rome and is mentioned by Pliny the Elder. The Spa's healing spring was reinvented in 1326 and reached its peak of popularity in the 18th century, when royalty began to visit it, learning of its healing properties. The name of this resort formed the basis of the medical direction - "spa therapy". The Spa still holds regular international exhibitions, fairs of spa preparations and mineral waters, and scientific symposia of balneologist scientists.The authors analyzed literary sources on this issue. A survey was conducted among qualified athletes of game sports and sports doctors in order to study the use of various types of SPA technologies in restoring the health of athletes after stress or illness.The results of a survey of athletes and sports doctors from various sports show that most often athletes use bath procedures and spa massage to restore their health. The use of these SPA procedures contributes to the improvement of the general state of health and recovery after training loads.At this stage of research, it became necessary to continue work in the direction of expansion and generalization of the obtained theoretical and practical findings, which can be applied in the practice of other types of sports.
Keywords: SPA-technology; varieties of spa; restoration; athletes; health